PENGARUH PAJAK TANGGUHAN, PROFITABILITAS, DAN LEVERAGE TERHADAP EARNINGS MANAGEMENT (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA BEI 2010-2017) - Ardli, Dwi Mulyo; Yuliandhari, Willy Sri (EDUTECH CONSULTANT, 2019)
This study aims to examine empirical evidence both simultaneously and partially about the effect of deferred tax, profitability, and leverage on earnings management in banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2010-2017. This study consisted of 200 samples at banking companies listed on the IDX in the period 2010-2017. This sample was obtained by purposive sampling. The analytical method used in this study is descriptive statistical analysis and panel data regression. The result showed that simultaneously deffered tax, profitability, and leverage had an effect on earnings management. While partially, deffered tax does not have effect on earnings management, profitability has a positive effect on earnings management, and leverage has a negative effect on earnings management.